A dosage-effect assessment of acute toxicology tests of microplastic exposure in filter-feeding fish. Issue 113 (June 2021) - Zhang, Chaonan; Wang, Jun; Pan, Zhengkun; Wang, Shaodan; Zhang, Li; Wang, Qiujie; Ye, Qiao; Zhou, Aiguo; Xie, Shaolin; Zeng, Fang; Xu, Guohuan; Zou, Jixing
Abstract: Abundant microplastics was found in aquatic ecosystem and aquatic organisms, which raised many concerns in public. Silver carp ( Hypophthalmichthys molitrix ), a species filter-feeding planktivorous fish, feed on particle between 4 and 85 μm in size, and the respiratory process works together with feeding mechanism when filtering plankton from water. The aim of this study was to assess the physiological response of silver carp exposed to 5 μm polystyrene microspheres during 48 h of exposure followed by 48 h of depuration through the gill histology, and oxidative stress biomarkers in intestine. The results revealed that microplastics can pass through the whole digestive tract of silver carp and be excreted by feces. Low microplastic concentration (80 μg/L) induced oxidative stress and up-regulation of TUB84 and HSP70 gene in intestine, and silver carp have ability to recover after the exposure to microplastic was removed. High microplastic concentration (800 μg/L) definitely cause significant damage to gills and intestines, in this situation, far beyond the possibility of fish own repair, and even when the threaten removed, silver carp can't recovery soon. Our studies assessed the dosage-effect relationship with physiological stress on silver carp when exposure to microplastics. Graphical abstract: Image 1 Highlights: Physiological response of silver carp exposed to 5 μm polystyrene microspheres were tested. Only low microplastic concentration induce oxidative stress and up-regulation of target gene in intestine. High microplastic concentration cause significant damage to gills and intestines. Silver carp can't recovery soon during depuration once high concentration microplastic exposure.